2020
DOI: 10.3389/fnins.2020.00253
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Structural and Functional Alterations of Frontal-Executive and Corticolimbic Circuits in Late-Life Depression and Relationship to Mild Cognitive Impairment and Dementia: A Systematic Review

Abstract: Depression is a risk factor for developing Alzheimer's disease and Related Dementia (ADRD). We conducted a systematic review between 2008 and October 2018, to evaluate the evidence for a conceptual mechanistic model linking depression and ADRD, focusing on frontal-executive and corticolimbic circuits. We focused on two neuroimaging modalities: diffusion-weighted imaging measuring white matter tract disruptions and resting-state functional MRI measuring alterations in network dynamics in late-life depression (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 126 publications
2
23
1
2
Order By: Relevance
“…One systematic review argued that there may be etiopathological mechanisms (e.g. a vascular pathway) that link elderly depression to cognitive impairment 15 . In addition, previous studies have indicated that deficits in attention, memory, and executive function appear during major depressive episodes 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…One systematic review argued that there may be etiopathological mechanisms (e.g. a vascular pathway) that link elderly depression to cognitive impairment 15 . In addition, previous studies have indicated that deficits in attention, memory, and executive function appear during major depressive episodes 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…In their voxel-based morphometry analysis, Karavasilis et al suggested that Alzheimer and depression comorbidities may be characterized by a specific pattern of gray matter loss that coincides with anatomical regions of the sensorimotor system and the right thalamus (71). In the same line, and as discussed earlier on, Rashidi-Ranjbar et al's work focused on two neuroimaging techniques, namely diffusionweighted imaging measuring white matter tract disruptions and resting-state functional MRI, to provide important clues on both functional and structural abnormalities shared by patients with late-life depression and/or MCI (38). Other studies show that [18F]-fluorodeoxyglucose (FDG) and amyloid-PET techniques allow in vivo assessment of regional glucose metabolism and betaamyloid plaque deposition, respectively, and their association with cognitive, behavioral, and physical performance in MCI and AD (72,73).…”
Section: Can Neuroimaging Ease the Diagnosis Of Depression In Ad?mentioning
confidence: 90%
“…As mentioned earlier, both disturbances appear to be linked through common neurobiological mechanisms (32,(36)(37)(38)(39), but it is still unclear whether depression is an etiological factor, a prodromal symptom, a coincidental finding or a secondary effect of dementia (12,27,28). Thus, manifestations of depression may not precede cognitive decline but arise in the presence of clinically overt dementia (46,47).…”
Section: What Factors Are Involved In the Etiology Of Depression In Tmentioning
confidence: 95%
See 2 more Smart Citations